Please don't gayify!: an autoethnographic account of medicalised relationality for LGBTQI+ safe affirming medical health education and clinical practice - Vicars, Mark; Deppeler, Mickey (Frontiers in Sociology, 2024)
In this article, the authors, a cis-gender gay man and an Indigenous non-binary, two-spirit person, narrate their past encounters with health professionals and their experiences pursuing allied health care training as students. Taking an autoethnographic approach, the first author re-narrates how medical practitioners and students engage (or fail to engage) with the LGBTQIA+ community. They draw on gray documentation derived from an interaction with a consulting physician that highlighted a telling lack of knowledge about the LGBTQ+ community, including those with diverse sex characteristics and sexualities/manifesting as unconscious bias. This interaction provided the impetus to speak back to the experience of being reduced to a medical prognosis. The second author questions the hegemonic practices underpinning encounters with the medical model of response in tertiary education. Our remit in this paper is to question how adequately the specific needs of the LGBTQI+ population are being addressed by the medical model and to what extent aspiring clinicians understand how their actions can contribute to gender- and sexuality-based discrimination and stigmatization.